Physician-related predictors of referral for multidisciplinary paediatric obesity management: a population-based study. (23rd March 2021) - Gehring, Nicole D; Kebbe, Maryam; Rathwell, Sarah; Perez, Arnaldo; Peng, Chenhui; Zendher, Emily; Ho, Josephine; Ball, Geoff D C
Abstract: Background: It is recommended that primary care-based physicians refer children with overweight and obesity to multidisciplinary paediatric obesity management, which can help to improve weight and health. Objective: To determine predictors of referral to multidisciplinary paediatric obesity management. Methods: This retrospective, population-level study included physicians who could refer 2–17 years old with a body mass index ≥85th percentile to one of three multidisciplinary paediatric obesity management clinics in Alberta, Canada. Physician demographic and procedural data were obtained from Practitioner Claims and Provider Registry maintained by Alberta Health from January 2014 to December 2017. Physician characteristics were compared based on whether they did or did not refer children for obesity management. Univariable and multivariable logistic regression models analysed associations between physician characteristics and referral making. Results: Of the 3863 physicians (3468 family physicians, 395 paediatricians; 56% male; 49.3 ± 12.2 years old; 22.3 ± 12.6 years since graduation) practicing during the study period, 1358 (35.2%) referred at least one child for multidisciplinary paediatric obesity management. Multivariable regression revealed that female physicians (versus males) [odds ratio (OR): 1.68, 95% confidence interval (CI): 1.46–1.93; P < 0.0001], paediatricians (versus family physicians) (OR: 4.89, 95% CI: 3.85–6.21; P < 0.0001) and urban-based physicians (versus non-urban-based physicians) (OR: 2.17, 95% CI: 1.79–2.65; P < 0.0001) were more likely to refer children for multidisciplinary paediatric obesity management. Conclusions: Approximately one-third of family physicians and paediatricians referred children for multidisciplinary paediatric obesity management. Strategies are needed to improve referral practices for managing paediatric obesity, especially among male physicians, family physicians and non-urban-based physicians as they were less likely to refer children. Lay Summary: Paediatric overweight and obesity impact one-third of children in Canada and the USA. It is recommended that physicians refer children with overweight and obesity to paediatric obesity management, which can help to improve their weight and health. While referral practices of US physicians have been well characterized, Canadian evidence remains limited. To address this gap, we examined predictors of referral making for paediatric obesity management. Our study included physicians (family physicians and paediatricians) who could refer 2–17 years old with overweight and obesity to three paediatric weight management clinics in Alberta, Canada between January 2014 and December 2017. Descriptive analyses and regression models were performed. Of the 3863 physicians practicing during the study period, 1358 (35.2%) referred at least one child for paediatric obesity management. Referring physicians were more likely to be female, paediatricians and practicing in urban-based clinics. Additional research is needed to explore physicians' decisions to refer children for obesity management, which can inform interventions to enhance referral, and ultimately, improve the health and well-being of children with obesity.